Answer:
The resultant polynomial is: [tex]6x^2-6x+5[/tex]
Step-by-step explanation:
We need to subtract [tex](x+1)^{2}[/tex] from [tex]7x^2-4x+6[/tex]
so, we start by performing the multiplication involved in the perfect square of the binomial [tex](x+1)[/tex], and obtain its expression in separate terms that can be combined:
[tex](x+1)^{2}=(x+1)\,(x+1)=x^2+x+x+1=x^2+2x+1[/tex]
Now we can subtract this trinomial from [tex]7x^2-4x+6[/tex], and combining like terms to get the resultant polynomial expression:
[tex]7x^2-4x+6-(x^2+2x+1)=7x^2-4x+6-x^2-2x-1=7x^2-x^2-4x-2x+6-1=6x^2-6x+5[/tex]
Then the resultant polynomial is: [tex]6x^2-6x+5[/tex]